Full mouth rehabilitation of the patient with severely mutilated dentition: a case report - Tyagi, Manjulika; Kusum, Chandan K. (International Journal Of Community Medicine And Public Health, 2022)
Management of the lost tooth structure by restoring the dental occlusion and aesthetics, is a challenging task for a dental clinician in full mouth rehabilitation cases. With the advent of new techniques and tooth-colored materials, it has become easy to meet demands of the patient. Full mouth rehabilitation involves restoring of dental occlusion, dental balance, and functionality with dental esthetics. This can be achieved through accurate clinical and radiographic examination, along with a diagnostic wax-up. Determining OVD is crucial in these cases. This paper describes the full-mouth rehabilitation of a 55-year-old patient with a severely mutilated dentition.